Синтез новых потенциальных β-адреноблокаторов аминопропанолового ряда - Р. С. Вартанян; Э. А. Адамян; М. А. Шейранян (ՀՀ ԳԱԱ հրատ.)
Предложены два способа осуществления реакций эпоксидов с аминами. Первый заключается во взаимодействии 1,2-эпокси-3-феноксипропана с аминоспиртами в условиях кислотного катализа, второй – в их взаимодействии в ДМСО без применения катализаторов. 1-Արիլօքսի-3-ամինապրոպանոլ-2- ի պրեպարատիվ ստացման պայմանների մշակման նպատակով ուսումնասիրվել է 1,2-էպօքսի-3-ֆենօքսիպրոպանի փոխազդեցության ռեակցիան մի շարք β- և γ- ամինասպիրտերի հետ: Առաջարկվել են ամինների և էպօքսիդների ռեակցիայի իրականացման երկու եղանակ` 1,2-էպօքսի-3-ֆենօքսիպրոպանի փոխազդեցությունը ամինների հետ թթվային կատալիզի պայմաններում և 1,2-էպօքսի-3-ֆենօքսիպրոպանի փոխազդեցությունը ամինասպիրտերի հետ ԴՄՍՕ-յում: In continuation of our investigations in the field of creation of new β-adrenoblockers two methods for realization of interaction of 1,2-epoxy-3-phenoxypropane with some β- and γ-aminoalcohols had been developed and proposed. The known methods for realization of this interaction did not satisfy our requirements due to the large amount of trap compounds accompaining the main product. The proposed first method is based on the employment of acidic catalysis for this interaction. The second one differs from known methods due to the employment of dimethylsulfoxide as a solvent for reagents interaction without any catalysator. This approaches allowed to obtain high yields of products to shorten reaction time, and to avoid formation of trap products.
Keywords: Organic Chemistry